Primary sources in online history learning: enhancing engagement and retention - Fahruddin Fahruddin; Arif Saefudin (Cogent Education, 2025)
This study aims to evaluate the effectiveness of primary sources in enhancing student engagement and retention in online history learning. The research uses a quasi-experimental design to assess the impact of integrating primary sources on student engagement and retention, involving 300 students from three high schools in Yogyakarta, Indonesia: SMAN 1, SMAN 5, and SMAN 8. Data collection was conducted through Likert-scale surveys and focus group discussions. The data analysis employed descriptive statistics, ANOVA to examine differences in engagement levels, and the Kruskal-Wallis test to evaluate retention scores. The results showed that 90% of students at SMAN 1 Yogyakarta, Indonesia, reported high satisfaction, while SMAN 5 and SMAN 8 showed satisfaction levels of 85% and 88%, respectively. ANOVA indicated significant differences in engagement (F = 8.76, p = 0.0002), with SMAN 1 scoring an average of 82, SMAN 8 scoring 80, and SMAN 5 scoring 78. The Kruskal-Wallis test revealed significant differences in retention (H = 21.36, p = 0.000023), with the highest median retention at SMAN 8 (77), followed by SMAN 1 (75), and SMAN 5 (72). These findings suggest that integrating primary sources significantly enhances student satisfaction, engagement, and retention in learning. This study provides new insights into the impact of authentic historical materials on student engagement and offers promising directions for developing more effective curricula. Furthermore, the study contributes to the global discourse on e-learning by demonstrating the value of primary sources in digital education, potentially guiding educational institutions worldwide in improving online history learning practices.